ANALISIS KORELASI WORK LIFE BALANCE ISLAMI TERHADAP KUALITAS KEPUTUSAN MANAJERIAL KEPALA MADRASAH TERKAIT MUTU - Utomo, Setio; Aimah, Siti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research is motivated by the importance of Islamic values-based work-life balance in supporting the quality of managerial decision-making by madrasah principals and improving the quality of education. The purpose of this study is to analyze the correlation between Islamic work-life balance and the quality of managerial decisions of madrasah principals and its implications for the quality of madrasah management. This study uses a qualitative approach with a case study research type conducted at MTs Al-Amiriyah Blokagung Banyuwangi. The research data sources consist of primary data obtained from the madrasah principal, vice-principals, and teachers, as well as secondary data in the form of institutional documents, madrasah policies, and supporting archives. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and thematic conclusion drawing, while data validity was checked using source and technique triangulation techniques. The results of the study indicate a positive correlation between Islamic work-life balance and the quality of managerial decisions of madrasah principals. Islamic work-life balance contributes to the emotional stability and clarity of thought of madrasah principals in making strategic decisions.